Imaginary home as a “middle ground”: the expression and experience of people with depressive disorder - Liu, Xinge; Peng , Zhaoyi; Zhao , Yifei (The Journal of Medicine, Humanity and Media, 2025)
In recent years, the number of depression patients has been rising, has become a modern syndrome, digital platform provides diversified expression channels for depression patients. This study adopts the depth interview and participatory observation research method, in the field of psychoanalysis "middle" theory as the breakthrough point, with little red book platform as the research object, the study found: depression patients with social media use is the paradox of contact and separation, social media become in the inner "middle zone" between the feeling and external reality. In this "middle ground", people with depression complete the construction of self, ego and superego through expression. While self-healing in human communication, it can also achieve mutual redemption in the community of depression patients. In this study, patients with depression, as different living individuals, explore their expression and experience in social media, and interpret the significance and value of social media for individuals with depression.